Electromanometry in biliary surgery: III. Action of duodenal dynamia on the automatism of the Oddi sphincter. The double command of the common bile duct cross - pancreatic - duodenal - Cosco Montaldo, Homero (Cirugía del Uruguay, 2020)
Presented at session 8th August 1962